Development of polyclonal antibodies against angiotensin type 2 receptors. - Reagan, L P (1993)
Murine neuroblastoma N1E-115 cells are a useful system in which to study neuronal angiotensin II (AngII) receptors. N1E-115 cells possess both type 1 (AT1) and type 2 (AT2) AngII receptor subtypes, as does mammalian brain. AT2 receptors in brain or N1E-115 cells can be solubilized in 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonate. In the present study, heparin-Sepharose chromatography was used to partially purify solubilized N1E-115 membranes to produce an enriched population of AT2 receptors. Subsequently, an eluted peak, containing the majority of AT2 binding activity, was used as an immunogen in the development of protein-directed polyclonal antibodies. The antibodies specifically detected immunoreactive proteins of approximately 110 and 66 kDa in both solubilized N1E-115 cells, as well as the original protein material that eluted from the heparin-Sepharose column, whereas no such immunoreactivity was detected in a kidney epithelial cell line that lacks any specific 125I-labeled AngII (125I-AngII) binding activity. Moreover, the antibodies immunoreacted with affinity-purified AT2 receptors. These antibodies were also able to immunoprecipitate AT2 receptors from solubilized N1E-115 cells, as revealed by the pharmacologic profile of 125I-AngII binding to the precipitated protein. Similarly, the antibodies were able to immunoprecipitate a 66-kDa protein that had been covalently crosslinked with 125I-AngII by use of the homobifunctional crosslinker dithiobis(succinimidyl propionate). Collectively, these results demonstrate the development of a specific AT2 receptor antibody that may be used to further characterize this receptor subtype at both the cellular and molecular levels.